Dynamics of telomere erosion and its association with genome instability in myelodysplastic syndromes (MDS) and acute myelogenous leukemia arising from MDS: a marker of disease prognosis? - Sieglová, Zuzana; Včelíková, Soňa; Čermák, Jaroslav; Žižková, Hana; Březinová, Dagmar; Dvořáková, Renáta; Marková, Markéta; Maaloufová, Jacqueline; Sajdová, Jana; Březinová, Jana; Zemanová, Zuzana; Michalová, Kyra (Leukemia research, 2004)
Telomere length was evaluated by terminal repeat fragment method (TRF) in 50 patients with myelodysplastic syndromes (MDS) and acute myelogenous leukemia (AML) arising from MDS and in 21 patients with untreated primary AML to ascertain, whether telomere erosion was associated with progression of MDS towards overt leukemia. Heterogeneity of TRF among MDS FAB subgroups (P=0.004) originated from its shortening in increased number of patients during progression of the disease. Chromosomal aberrations were present in 32% MDS patients with more eroded telomeres (P=0.022), nevertheless a difference between mean TRF in the subgroups with normal and abnormal karyotype diminished during progression of MDS. A negative correlation between individual TRF and IPSS value (P=0.039) showed that telomere dynamics might serve as a useful prognostic factor for assessment of an individual MDS patient's risk and for decision of an optimal treatment strategy.
Keywords: Risk Factors; karyotypizace; progrese nemoci; nestabilita genomu; Adolescent; Myelodysplastic Syndromes; prognóza; chromozomální aberace; Child; Telomere; Karyotyping; dítě; Adult; akutní myeloidní leukemie; Aged; dospělí; senioři; Disease Progression; Genomic Instability; mladiství; myelodysplastické syndromy; Chromosome Aberrations; senioři nad 80 let; lidé; Biomarkers, Tumor; Humans; telomery; rizikové faktory; Aged, 80 and over; Prognosis; lidé středního věku; nádorové biomarkery; Leukemia, Myeloid, Acute; Middle Aged